2017
DOI: 10.1007/s10803-017-3268-0
|View full text |Cite
|
Sign up to set email alerts
|

Parent-Mediated Intervention for One-Year-Olds Screened as At-Risk for Autism Spectrum Disorder: A Randomized Controlled Trial

Abstract: Theoretically, interventions initiated with at-risk infants prior to the point in time a definitive autism spectrum disorder (ASD) diagnosis can be made will improve outcomes. Pursuing this idea, we tested the efficacy of a parent-mediated early intervention called Adapted Responsive Teaching (ART) via a randomized controlled trial with 87 one-year-olds identified by community screening with the First Year Inventory as at-risk of later ASD diagnoses. We found minimal evidence for main effects of ART on child o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
182
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(187 citation statements)
references
References 83 publications
5
182
0
Order By: Relevance
“…Children were subsequently followed throughout early childhood with comprehensive developmental assessments conducted at three time points. Although the primary aim of the earlier study was to test the efficacy of a parent-mediated intervention (Watson et al, in press), and thus children were assigned to treatment (Adapted Responsive Teaching) versus control (Referral to Early Intervention and Monitoring) conditions, there were no main effects of treatment on any of the primary child outcomes of interest in the RCT or on any of the variables relevant to the present study. Additionally, we demonstrate that significant effects observed in this report do not vary according to children’s treatment group assignment (see Exploration of Alternative Explanations in Results).…”
Section: Methodsmentioning
confidence: 96%
“…Children were subsequently followed throughout early childhood with comprehensive developmental assessments conducted at three time points. Although the primary aim of the earlier study was to test the efficacy of a parent-mediated intervention (Watson et al, in press), and thus children were assigned to treatment (Adapted Responsive Teaching) versus control (Referral to Early Intervention and Monitoring) conditions, there were no main effects of treatment on any of the primary child outcomes of interest in the RCT or on any of the variables relevant to the present study. Additionally, we demonstrate that significant effects observed in this report do not vary according to children’s treatment group assignment (see Exploration of Alternative Explanations in Results).…”
Section: Methodsmentioning
confidence: 96%
“…Parents were recruited from the EDP‐2 FYI database (i.e., all returned FYIs for the Watson et al, study) when their children were within 1 month of 42 months (3.5 years) of age. The database included contact information for parents who filled out the FYI 2.0 when their children were 12 months and who agreed to be contacted for follow‐up studies.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers obtained completed FYIs from the parents of more than 8,700 children over the course of a multiyear study. Infants who scored above a certain criteria on two domains of risk (Social‐Communication [S‐C] and Sensory‐Regulatory [S‐R]) were flagged as “at risk” for an eventual diagnosis of ASD and were invited to participate in the Early Development Project‐2, a randomized controlled trial of an early intervention [Watson et al, ]. Infants whose FYI 2.0 scores did not meet the “at risk” criteria were available for other research projects, and a subset of parents of these children constituted the sample of the present study.…”
Section: Introductionmentioning
confidence: 99%
“…The ART group also exhibited greater gains in language performance and reduction in hypo-responsiveness on parent-report measures. Although these child treatment effects were not observed in a replication study, treatment effects on parent responsiveness and parent production of positive affect during parent–child interactions were identified (Watson et al, 2017). Watson et al (2017) reported considerable evidence for mediation of the effect of group assignment on child outcomes via changes in parent responsiveness, despite the general lack of main effects when parent responsiveness was not accounted for in the models.…”
Section: Naturalistic Developmental Behavioural Intervention (Ndbi) Amentioning
confidence: 99%
“…Although these child treatment effects were not observed in a replication study, treatment effects on parent responsiveness and parent production of positive affect during parent–child interactions were identified (Watson et al, 2017). Watson et al (2017) reported considerable evidence for mediation of the effect of group assignment on child outcomes via changes in parent responsiveness, despite the general lack of main effects when parent responsiveness was not accounted for in the models. The lack of change in control parents’ responsiveness and a decrease in their affect, compared to the ART parents’ gains in both of these domains, implies a protective effect of training parents in use of responsive strategies (Strain & Bovey, 2011; Watson et al, 2017).…”
Section: Naturalistic Developmental Behavioural Intervention (Ndbi) Amentioning
confidence: 99%